Prognostic and clinicopathological value of systemic immune-inflammation index in patients with osteosarcoma: a meta-analysis - Wang, Xiaoyan; Wu, Zhong; Zhang, Zongxin; Jiang, Ziwei (Frontiers in Immunology, 2024)
Background: The efficiency of systemic immune-inflammation index (SII) in predicting prognosis of osteosarcoma (OSA) patients has been extensively analyzed, but no consistent findings are obtained. Therefore, this meta-analysis focused on identifying the precise prognostic value of SII for OSA. Methods: We comprehensively searched electronic databases of PubMed, Embase, Web of Science, Cochrane Library, and China National Knowledge Infrastructure (CNKI) from inception to 24 February, 2024. Meanwhile, the efficiency of SII in predicting prognosis of OSA was evaluated by calculating pooled hazard ratios (HRs) as well as 95% confidence intervals (CIs). Additionally, the correlation of SII with the OSA clinicopathological characteristics was analyzed based on pooled odds ratios (ORs) and 95%CIs. Results: Six studies with 1015 cases were enrolled into this work. According to the combined data, the higher SII was markedly related to poor overall survival (OS) (HR=2.01, 95%CI=1.30-3.09, p=0.002) and Enneking stage III (OR=2.21, 95%CI=1.11-4.39, p=0.024) of patients with OSA. Nonetheless, SII was not significantly related to gender, age, pathological fracture, tumor size, tumor location, tumor differentiation, and metastasis in patients with OSA. Conclusions: In summary, the higher SII is markedly related to poor OS and advanced Enneking stage in OSA patients.